Bangladeshi 'Boat People': Context, Drivers And Policy Implications. (February 2019) - Hasan, Mubashar
Based on field research, this article focuses on the little-known phenomenon of Bangladeshi 'boat people' seeking entry to Thailand and Malaysia. It identifies how in a populous country of the Global South, familiar with various kinds of worker migration and movements of people, changing political, social and ecological contexts may generate and drive yet more manifestations of migration, also related to trafficking. In particular, certain developments in international relations connected to religious politics are shown to be instrumental in facilitating migration through legal and illegal channels. The interviews identify significant motivating factors that suggest an urgent need to develop policy recommendations, also in South Asia, to alleviate risks and suffering for irregular migrants and their families.